Nuclear Polyhedrosis Virus A potential biopesticide of insect-pest - Varshney, Richa; Rachana, R R; Romila, Romila (Indian Farming, 2017)
NPV can be an ideal tool for use in IPM programme because it is having less residual toxicity, compatible with many chemicalpesticides, self-perpetuating nature and ecofriendly. To make it more effective, there is urgent need to develop more virulent and potent strains by biotechnological methods. Other areas which require attention are to develop quality control guidelines and methodologies, systematic registration policies, to identify effective strains and to develop UV (Ultraviolet) resistant strains. Finally to develop stronger IPM strategies, it is necessary to study interaction of NPV with other control measures thoroughly.